Spectrum of central nervous system infections in neurosciences hospital in two years : a retrospective study - Jawad, Aiyar Shakir (AL-Kindy College Medical Journal, 2020)
Background :Infectious disorders in general have high morbidity and mortality.. CNS infections include many disorders like bacterial meningitis, tuberculous and other subacute and chronic meningitis, viral meningitis, cerebral abscess, spinal cord infections, and others. Objective: To assess our locality about prevalence of CNS infections , to have more awareness regarding CNS infections, and to try to find the proper way to reduce their prevalence and to treat them in appropriate way. Method :We revised the records of all the cases of CNS infections excluding cases of spinal cord infections who were admitted in the wards of neuroscience hospital over the previous two years ( from July/2010 to June 2012 ),those were 132 cases.Seasonal incidenceand other clinical aspects and other parameters like age , sex, , fever are extracted and recorded Results: The most common CNS infections in sequence from the most to the least were bacterial meningitis, viral encephalitis, tuberculous meningitis, viral meningitis, and cerebral abscess. The most common age group which is affected by CNS infections was below 10 years. Males are affected more than females taking in consideration all types of infection. P values were statistically significant for age, fever, signs of meningeal irritation, focal neurological deficit, and seizures. Conclusion : The total rate of admission of CNS infections in our series was lower than other study. The most frequent type of CNS infections was bacterial meningitis which is the same as most of the studies. Males are affected more than females in our study in all types of CNS infections, this was approximate to other studies except for tuberculous meningitis. Bacterial meningitis and viral encephalitis were more common in preschool children in our study. Fever rate in bacterial and tuberculous meningitis was different from other studies. Seizure rate in bacterial meningitis and viral encephalitis was approximate to other results. Rate of focal deficit in viral encephalitis and tuberculous meningitis was different from other studies. Rate of CSF protein elevation in all CNS infections was approximate to other studies. Rate of hypoglycorrhachia was different from other studies only in tuberculous meningitis. CSF pleocytosis was approximate to other studies in all types of CNS infections. The two most common types of CNS infections , bacterial meningitis and viral encephalitis, are more common in preschool age groups.